2022
DOI: 10.1108/maj-05-2021-3157
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and firm risk: international evidence

Abstract: Purpose This paper aims to uncover the global trend on the relationship between board gender diversity and firm risk. In addition, this paper investigates how country characteristics affect the relationship between board gender diversity and firm risk. Design/methodology/approach This study uses a large sample of firms in 45 countries for the period from 2002 to 2018. Ordinary least square regression is used as a baseline methodology, along with firm fixed effects. Difference-in-differences regression, two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 77 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…(2019) revealed a negative relationship between women on boards and firm risk, but a positive impact of women on boards and firm risk on profitability. The study further reported a positive significant impact of women on boards on observable dynamics of the board, thus supporting the group dynamics mechanism through which women on boards may reduce risk but improve profitability, and hence nullifying the stereotypical misconception of women as generally being risk averse (Li et al, 2022;Ozdemir and Erkmen, 2022). Janssen (2019) also demonstrated in his thesis how EM and gender diversity complement in explaining firm performance, in that, EM mediates as well as moderates the relationship between gender diversity and performance of firms sampled from ten countries of the European Economic Area without a gender quota.…”
Section: Earnings Management and Firm Performance: The Moderating Rol...mentioning
confidence: 52%
See 1 more Smart Citation
“…(2019) revealed a negative relationship between women on boards and firm risk, but a positive impact of women on boards and firm risk on profitability. The study further reported a positive significant impact of women on boards on observable dynamics of the board, thus supporting the group dynamics mechanism through which women on boards may reduce risk but improve profitability, and hence nullifying the stereotypical misconception of women as generally being risk averse (Li et al, 2022;Ozdemir and Erkmen, 2022). Janssen (2019) also demonstrated in his thesis how EM and gender diversity complement in explaining firm performance, in that, EM mediates as well as moderates the relationship between gender diversity and performance of firms sampled from ten countries of the European Economic Area without a gender quota.…”
Section: Earnings Management and Firm Performance: The Moderating Rol...mentioning
confidence: 52%
“…Boadi et al (2022), whose study supports pro-gender diversity on boards, demonstrate that greater boardroom gender diversity generates technical efficiencies for banks in Ghana. Li et al (2022) also found that board gender diversity is associated with lower firm risk worldwide. The results of Guizani and Abdalkrim (2022) also show that board gender diversity could help to improve board effectiveness by preventing corporations from being too exposed to financial distress and bankruptcy.…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 92%
“…Firm risk-taking is measured by the stock return volatility as a proxy for firm risk, which captures total risk, including firm-specific risk and market risk. Previous finance studies have frequently adopted stock return volatility as a proxy of firm total risk (Hurley & Choudhary, 2020;Achour, 2021;Mastella et al, 2021;Li et al, 2022). Board gender diversity is measured by: (1) Gender variety in a board is formulated by the Feblau Index, (2).…”
Section: Methodsmentioning
confidence: 99%
“…Abou-El-Sood, (2021) Finding the Board's gender diversity positively influences corporate risk-taking. Li et al, (2022) It found the board's gender diversity was negatively associated with corporate risk.…”
Section: Company Businessmentioning
confidence: 99%